Dialogic Consensus as the Moral Philosophical Basis for Shared Decision-making. (May 2019) - Walker, Paul
Shared decision-making is important and beneficial for patients. Practically, this requires that we explore the values of the patient and the clinician and then consider available treatment options. The aim is to maximize the good of the patient in the context of their illness. Hence, clinical consultations are situations in which we can, and should, draw upon moral philosophical precepts. One such precept, which can fortify the foundations of shared decision-making, is a process of inclusive, noncoercive, and reflective dialogue, which aims at reaching a consensual decision as to what is best for the patient in their situation. Summary: Shared decision making is important and helpful for patients. This is based upon having a conversation about values and what is important. We can base that conversation on principles of moral philosophy, via a process termed "dialogic consensus".